The Impact of The Management of Zakat, Infaq, and Shadaqah on the Social-Based Program of the Sumedang Sehat based on Social Return on Investment (SROI) (Case Study of BAZNAS Sumedang Regency) (UIN Sunan Kudus, 2021)
Various programs have been presented for the distribution of zakat, donations, and shadaqah that have been collected. The purpose of zakat, infaq, and shadaqah is not only to help the poor related to consumptive things, but it also has a permanent goal, that is to alleviate poverty. One goal of the Sustainable Development Goals (SDGs) in the first of the 17 goals and 169 targets, specifically ending poverty in any form and anywhere. In addition, there are still benefits from zakat, donations, and alms for mustahics, including the health sector. The Sumedang Sehat program is a BAZNAS program in the Sumedang Regency in the health sector. As one program established and funded by BAZNAS Sumedang District, the Sumedang Sehat program requires evidence of the impact and how much impact it has on the program in order to be transparent about the zakat, infaq, and alms funds that have been distributed. This study aims to calculate the impact of a BAZNAS program, namely the Sumedang Sehat program, using social return on investment (SROI). The results of this study showed an SROI ratio of 51.22:1. Every IDR 1 invested resulted in IDR 51.22, which benefits both economically, socially, and environmentally. This means that the Sumedang Sehat program has provided benefits 51.22 times greater than the value of the invested input.